2020
DOI: 10.3390/s20216391
|View full text |Cite
|
Sign up to set email alerts
|

Enhancements and Challenges in CoAP—A Survey

Abstract: The Internet of Engineering Task (IETF) developed a lighter application protocol (Constrained Application Protocol (CoAP)) for the constrained IoT devices operating in lossy environments. Based on UDP, CoAP is a lightweight and efficient protocol compared to other IoT protocols such as HTTP, MQTT, etc. CoAP also provides reliable communication among nodes in wireless sensor networks in addition to features such as resource observation, resource discovery, congestion control, etc. These capabilities of CoAP hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 54 publications
0
15
0
1
Order By: Relevance
“…However, this calculation is limited to only the first transmission and first retransmission. CoCoA+ is unable to select the correct RTO value for bursty traffic [10].…”
Section: Background and Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this calculation is limited to only the first transmission and first retransmission. CoCoA+ is unable to select the correct RTO value for bursty traffic [10].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Inaccurate measurements of RTTs can lead to spurious retransmissions. The authors in [9], [10], [11], [12] indicated that CoCoA+ performed significantly worse than the basic CoAP in various network conditions, especially for bursty traffic.…”
Section: Background and Related Workmentioning
confidence: 99%
See 3 more Smart Citations